1997
DOI: 10.1177/1046878197281004
|View full text |Cite
|
Sign up to set email alerts
|

Trappings of Expertise and the Pursuit of Failure

Abstract: This article explores some of the basic shortcomings and fallacies of managerial behavior in dynamic situations. In a laboratory study, 20 groups of three participants each, all with an education in business management, were observed while trying to manage a computer-simulated industrial organization called MANUTEX. This is an interactive simulation of a small garment factory. For most groups, this problem proved to be extremely difficult. The analysis of the problem-solving process and the strategies that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Previous research has indicated that adult decision makers tend to have cognitive biases and errors when dealing with complex problems (Ramnarayan, Strohschneider, & Schaub, 1997). Fiske and Taylor (1991) put forward that decision makers tend to be "cognitive misers," minimizing cognitive effort by neglecting nongains or nonlosses in their planning.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that adult decision makers tend to have cognitive biases and errors when dealing with complex problems (Ramnarayan, Strohschneider, & Schaub, 1997). Fiske and Taylor (1991) put forward that decision makers tend to be "cognitive misers," minimizing cognitive effort by neglecting nongains or nonlosses in their planning.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this study sheds light on the contradicting expert-rigidity versus expert-flexibility models. Although decision-making strategies in business experts and novices have been described in case studies [71] and in the field of cognitive psychology and engineering [72,73,74], as well as in the field of politics [75], they have been rarely investigated empirically and validated by connecting them to performance.…”
Section: Discussionmentioning
confidence: 99%
“…Solving complex problems requires continuous learning-asking the right questions rather than rushing in with answers borrowed from contexts that do not translate (Grint, 2005(Grint, , 2008(Grint, , 2010. Failure to operate in this way results in challenges ranging from actions not matching the urgency of data, lack of awareness of the broader context, operating from false assumptions that become hard to dislodge, and holding to an initial plan despite poor evidence or support (Ramnarayan & Schaub, 1997). Complex problem solving requires iterative knowledge acquisition and application, and a structure that will support adaptive planning and response.…”
Section: Problem/impetusmentioning
confidence: 99%